Evaluation Model and Its Urgency on Elementary Education Programs - Suklani Suklani (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Evaluation of an education program is a process of systematic activity to see how successful the planned education program is and to provide information to stakeholders in order to make a decision. The problem that often occurs is that the object of evaluation in education is still focused on the learning process, even though the evaluation includes all educational components and programs in a comprehensive manner. The purpose of this research is to describe program evaluation models and their urgency in evaluating educational programs. The novelty of this study is the implementation of various evaluation models in elementary education. The results of this study indicate that there are more than 50 program evaluation models, of which there are five program evaluation models that can be applied in evaluating educational programs, namely the Context, Input, Process, Product (CIPP), outcomes (CIPPO), Provus, Countenance (Stake), and Kirkpatrick evaluation models. The contribution is that with this evaluation information will be obtained about the achievements of the educational program, including its quality, effectiveness, efficiency and productivity, so that a decision can be made whether the program is worth continuing, revising, stopping or reformulating so that goals, objectives, processes can be found from the previous one